THE EFFECT OF EXTRINSIC MOTIVATION AND INSTRINSIC MOTIVATION AGAINST LEARNING ACHIEVEMENTS OF FOOD AND BEVERAGE SERVICE STUDENT AK. MAPINDO, ACADEMIC YEAR 2018/2019 - EKADHARMA SUSILA, BAGUS PUTU; ARIANTINI, NI PUTU OKA (Akademi Komunitas MAPINDO, 2019)
This study aims to determine the effect of extrinsic motivation and instrinsic motivation on learning achievement students in the Food & Beverage Service Program Study, Akademi Komunitas Manajemen Perhotelan Indonesia academic year 2018/2019. The questionnaire distributed to 57 respondents was all members of the population. This study, using regression analysis techniques by testing hypotheses using t test and F test. The t-test results show that extrinsic motivation has a positive and significant effect on student achievement in the Food & Beverage Service Program Study, Akademi Komunitas Manajemen Perhotelan Indonesia academic year 2018/2019. This is seen from the results of the regression coefficient X1(b1) thitung = 6.977 > ttable (0.05: 54) = 1.6736 and sig t = 0,000 (p < 0.05). Intrinsic motivation has a positive and significant effect on student learning achievement in the Food & Beverage Service Program Study, Akademi Komunitas Manajemen Perhotelan Indonesia academic year 2018/2019. This is seen from the results of the regression coefficient X1(b1) thitung = 3.743> ttable (0.05: 54) = 1.6736 and sig t = 0,000 (p <0.05). Extrinsic motivation and intrinsic motivation have a positive and significant effect on student achievement in the Dish Study Program, Indonesian Hospitality Management Community Academy academic year 2018/2019. This is based on the results of the F statistical test (ANOVA) where Fcount = 32.521 > F table = 3.17 with sig F = 0,000 (p < 0.05). Other information obtained from the results of the above analysis that extrinsic motivation has a more dominant influence on learning achievement when compared with intrinsic motivation Keywords: Extrinsic Motivation, Intrinsic Motivation, Learning Achievement